Effect of baseline serum vitamin D level on symptom and medication scores of subcutaneous immunotherapy in children with mite allergy - Jia, Xiaoxiao; Zheng, Hang; Yan, Xiumei; Dai, Huan; Xiang, Qiangwei (Frontiers in Pediatrics, 2022)
Introduction: Allergen immunotherapy (AIT) is considered to be the only treatment that may change the natural process of allergic diseases. Subcutaneous immunotherapy (SCIT) is a type of allergen immunotherapy that is commonly used in clinical practice. However, SCIT has inconsistent effects on individuals, and it is yet unclear what factors affect therapeutic efficacy. In recent years, vitamin D levels have been speculated as a potential factor influencing SCIT efficacy. Objective: To investigate the effect of serum vitamin D level on the SCIT efficacy in children with allergic rhinitis and/or asthma caused by dust mite allergy. Methods: According to the panel consensus, children with asthma and/or allergic rhinitis who received SCIT were divided into the vitamin D deficiency group (<12 ng/mL), vitamin D insufficiency group (12-20 ng/mL), and vitamin D sufficiency group (>20 ng/mL). Serum 1-25(OH) D3, blood eosinophil, total IgE, dermatophagoides pteronyssinus (Dp), and dermatophagoides farina (Df) specific IgE (sIgE) were detected, and questionnaires of symptom and medication scores were collected before and after one year of treatment. Results: After one year of SCIT treatment, the symptom and medication score significantly decreased (P<0.05), but there was no difference between the efficacy in different groups (P>0.05). Our study found a statistical difference in Dp sIgE level between the vitamin D deficiency and the sufficiency groups (P=0.024), and vitamin D levels become lower with children's growth (Y=-0.8981*X+34.26, P=0.0025). Conclusions: No difference was found between the efficacy of one-year SCIT and serum vitamin D levels based on symptom and medication scores. Nevertheless, higher vitamin D levels may be associated with a decreased indicator of Dp allergy.